A citizens' jury on regulation of McDonald's products and operations in Australia in response to a corporate health impact assessment - Julia Anaf; Fran Baum; Matthew Fisher (Elsevier, 2018)
Abstract Objectives: 1) To report outcomes from a citizens' jury examining regulatory responses to the health impacts of McDonald's Australia; 2) To determine the value of using citizens' juries to develop policy recommendations based on the findings of health impact assessment of transnational corporations (TNCs). Methods: A citizens' jury engaged 15 randomly selected and demographically representative jurors from metropolitan Adelaide to deliberate on the findings of a Corporate Health Impact Assessment, and to decide on appropriate policy actions. Results: Jurors unanimously called for government regulation to ensure that transnational fast food corporations pay taxes on profits in the country of income. A majority (two‐thirds) also recommended government regulation to reduce fast food advertising, and improve standards of consumer information including a star‐ratings system. A minority held the view that no further regulation is required of the corporate fast food industry in Australia. Conclusion: The jury's recommendations can help inform policy makers about the importance of ending the legal profit‐shifting strategies by TNCs that affect taxation revenue. They also endorse regulating the fast food industry to provide healthier food, and employing forms of community education and awareness‐raising. Implications for public health: Citizens' juries can play an important role in providing feedback and policy recommendations in response to the findings of a health impact assessment of transnational corporations.